Customer service quality and benchmarking in public transport contracts - David A. Hensher (International Journal of Quality Innovation, 2015)
As contracting of public transport services increases in sophistication, there is a growing focus on an increasing number of key performance indicators that emphasis service quality. Although contracts won under competitive tendering or by negotiation are assessed on a number of evaluation criteria, cost efficiency still remains the main basis for selecting a preferred operator. There has been a limited effort to identify the service quality influences that really matter to users of public transport. Ways of incorporating the packaging of service quality offer an improved and behaviourally richer way of representing the role of underlying dimensions of quality in establishing how well a contracted service is delivering services to satisfy customers. In this paper we present a way of doing this using a construct called a Customer Service Quality Index (CSQI), in which a stated preference survey together with actual experience in using public transport is used to obtain preference weights for each significant attribute defining service quality, and which is used then to establish a CSQI for each sampled user, and by aggregation, the performance on service quality of each operator. Such a measure should be considered by regulators when both assessing the merits of each operator's bid in order to avoid the real risk that cost efficiency dominates at the expense of gains in service performance and in ongoing monitoring of performance.
Keywords: 650; Customer service quality; Benchmarking; Bus contracts; Stated preference surveys; Logit models